Two Hits Are Better than One: Membrane-Active and DNA Binding-Related Double-Action Mechanism of NK-18, a Novel Antimicrobial Peptide Derived from Mammalian NK-Lysin - Yan, Jiexi (American Society for Microbiology, 2013)
The extensive use and misuse of antibiotics in medicine result in the emergence of multidrug-resistant bacteria, creating an urgent need for the development of new chemotherapeutic agents. Nowadays, antimicrobial peptides are widely recognized as a class of promising candidates with activity against multidrug-resistant bacteria. NK-18 is a truncated peptide derived from NK-Lysin, an effector of cytotoxic T cells and natural killer cells. In this study, we studied the antibacterial mechanism of action of NK-18. The results revealed that NK-18 has potent antibacterial activity against Escherichia coli and Staphylococcus aureus. According to our findings, NK-18 is membrane active and its target of action is not only the bacterial membrane but also the DNA in the cytoplasm. The double targets of NK-18 make it difficult for bacteria to generate resistance, which may present a new strategy to defend against multidrug-resistant bacteria and provide a new lead in the design of potent antimicrobial peptides with therapeutic application in the presence of increasing resistance to conventional antibiotics.